Tracking the changing feature of a moving object - De Freitas, J; Myers, N; Nobre, A (Association for Research in Vision and Ophthalmology, 2016)
The mind can track not only the changing locations of moving objects, but also their changing features, which are often meaningful for guiding action. How does the mind track such features? Using a task in which observers tracked the changing orientation of a rolling wheel's spoke, we found that this ability is enabled by a highly feature-specific process which continuously tracks the orientation feature itself--even during occlusion, when the feature is completely invisible. This suggests that the mental representation of a changing orientation feature and its moving object are continuously transformed and updated, akin to studies showing continuous tracking of an object's boundaries alone. We also found a systematic error in performance, whereby the orientation was reliably perceived to be further ahead than it truly was. This effect appears to occur because during occlusion the mental representation of the feature is transformed beyond the veridical position, perhaps in order to conservatively anticipate future feature states.